A Energy Efficiency Strategy in Manufacturing Industry Through Implementation of Automation Technology - Gede Arya Rachman; Rifki Saiful; Ratna Ariati; Syukri M. Nur; Erkata Yandri (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
The implementation of automation technology in the manufacturing industry has become a critical solution in facing global energy efficiency challenges. Amid increasing demands for reduced energy consumption and carbon emissions, the manufacturing sector is required to adopt innovative solutions in their operations. This study aims to analyze and evaluate energy efficiency strategies through the application of automation technology in the manufacturing sector, with a focus on optimizing energy consumption and increasing productivity. The research methodology uses both quantitative and qualitative approaches, including analysis of historical energy consumption data from 50 manufacturing facilities that have implemented automation systems, in-depth interviews with industry experts, and comparative evaluation of various automation technologies available in the market. The results show that the implementation of automation technology can reduce energy consumption by an average of 27.5% in the first 12 months, with an increase in production efficiency by 35%. Further analysis reveals that automation systems based on the Internet of Things (IoT) and artificial intelligence provide optimal results in energy management, with an average return on investment of 2.3 years. The integration of smart sensors and automated control systems has proven to be effective in optimizing energy use in production processes, predictive maintenance, and peak load management. The study also identified key challenges in implementation, including high initial investment costs, personnel training needs, and the complexity of system integration. The study found that key factors for successful implementation include strategic planning, top management support, and a comprehensive training program. In conclusion, the application of automation technology in the manufacturing industry is an effective strategy to achieve long-term energy efficiency, with the potential for significant savings and increased industrial competitiveness.